Burocracia e poder : um estudo cr??tico sobre o uso dos sistemas de informa????o em uma empresa de cr??dito ao consumidor - Batista, H??lio (2003)
In this research we define social actors interests as a complex set of predisposition embracing goals, values, desires, expectations and other orientations and inclinations that lead a person to act in one direction rather than another. Organizations rules define areas of concern that social actors wish to reserve or enlarge, positions that they wish to protect or achieve. We show in our study that an organization is a political arena that define ???areas??? where social actors interests collide. Fortunate social actors are able to control fundamental resources for the organization they belong. They have some kind of knowledge or know-how the organizational group need for its survival. In this case, these social actors earn more power in the organization and they are able to negotiate advantages and benefits. Our study show how information systems can be used for a group of social actors to preserve their interests and to increase its power in the organization.